A Contrastive Study of English and Igala Segmental Phonemes: Implications for ESL Teachers and Learners - Unubi, Abraham Sunday (British Journal of Healthcare and Medical Research, 2019)
This paper investigated a contrastive study of English and Igala segmental phonemes: implications for English as a Foreign Language (EFL) teachers and learners. A contrastive analysis is a linguistic tool used in comparing two unrelated languages, and the main objective of it is to bring out the differences in the two languages compared with a view to emphasising on the effects which such differences have on both EFL teachers and learners. This research appealed only to the secondary sources of data, which included the orthographies of both languages under study. The Igala orthography was obtained from the department of Igala Language and Culture, Kogi State College of Education Ankpa, in addition to other material in Igala. The consonant and vowel phonemes of the two languages were placed contiguously in a tabular form and given appropriate heading to be able to observe their level of differences and similarities easily. Then words in which these phonemes occur in the Igala language were supplied and the phonemes indicated. Some of the findings of this research revealed the following: (i) that the consonant phonemes such as /ð/, /θ/, /s/, /ʃ/, /ʒ/, /v/ and /z/, and the vowel phonemes /ǝ/ and /ʌ/, which are present in English are however absent in Igala, just as /kp/, /gb/, /ny/, /kw/, /gw/ and /nw/ that are present in Igala are absent in English; (ii) English has twelve pure vowels (monophthongs) and eight diphthongs, while Igala has fourteen monophthongs and eleven diphthongs; (iii) that these differences have posed certain teaching and learning difficulties to both EFL teachers and learners who are native speakers of the Igala language; and (iv) that while English has twenty-four consonant phonemes, Igala has twenty-three.